Stapes and Stapes Revision Surgery: Preoperative Air-Bone Gap Is a Prognostic Marker. Issue 7 (August 2021) - Sharaf, Kariem; Grueninger, Ivo; Hilpert, Annalena; Polterauer, Daniel; Volgger, Veronika; Manz, Kirsi; Canis, Martin; Hempel, John Martin; Müller, Joachim
Abstract : Objective: Stapes surgery is considered an effective treatment in otosclerosis, but controversy remains regarding predictors of surgical outcome. Study Design: Retrospective cohort study. Setting: Tertiary referral center. Patients: One hundred sixty three cases of stapes surgery between 2012 and 2019 were reviewed. Main Outcome Measures: Primary outcome measures were relative hearing improvement (relHI), defined as preoperative minus postoperative air conduction divided by preoperative air-bone gap (ABG), as well as relative ABG closure (relABGc), defined as preoperative ABG minus postoperative ABG divided by preoperative ABG. Univariate and multivariate linear regression analyses were performed to determine independent predictors for these outcomes. Results: Higher preoperative bone conduction (BC) and primary surgery (compared with revision) were independently associated with increased relHI ( p  = 0.001 and p  = 0.004, respectively). Lower preoperative BC, higher preoperative ABG, primary surgery, and age were independently associated with increased relABGc ( p  = 0.0030, p  < 0.001, p  = 0.0214, and p  = 0.0099, respectively). Sex did not predict surgical outcome. In patients with less than 20 dB preoperative ABG, likelihood of negative relABGc was increased (compared with 20–30 dB or >30 dB preoperative ABG, p  = 0.0292, Fisher's exact test). This tendency was not significant for relHI ( p  = 0.074). Conclusions: Our findings demonstrate that calculating HI and ABGc in relation to preoperative ABG can reliably predict outcomes of stapes surgery. Both primary and revision stapes surgery are effective treatment options, but relative improvement is higher in primary cases. Preoperative BC, preoperative ABG, and age predict surgical outcomes as well. Otosclerosis patients with low preoperative ABG, especially less than 20 dB, should be counseled and selected cautiously regarding stapes surgery. Abstract : Supplemental Digital Content is available in the text